SARS-CoV-2: detecção colorimétrica e eletroquímica do RNA viral em amostras de saliva humana - Miranda, Wyllian Neves (Universidade Federal de São Carlos, 2025)
SARS-CoV-2: Colorimetric and electrochemical detection of viral RNA in human saliva samples. The emergence and rapid spread of respiratory and systemic viruses have significantly marked the global health scenario in recent decades. From HIV to SARS-CoV-2, viral agents have caused health crises with high human and economic costs, reinforcing the importance of effective surveillance, diagnosis, and containment strategies. Despite the reduction in deaths due to vaccination, mass testing remains an essential measure, but still insufficient in Brazil due to limitations in cost, accessibility, and infrastructure. This work aimed to develop simpler, faster, and lower-cost molecular assays for the detection of SARS-CoV-2 RNA in saliva samples. Two methods were proposed: a colorimetric method, compatible with microtubes or 96-well microplates, and an electrochemical method, applicable in unit cells or arrays of eight cells. The assays are based on the use of magnetic particles functionalized with carboxyl groups to capture the target by anchoring DNA probes complementary to the sequences of the N gene, present in the SARS-CoV-2 RNA. Detection and quantification are performed without the need for electrode modification, extraction or amplification of genetic material. The experimental conditions were optimized and tested both on fortified saliva samples and on real samples from patients already diagnosed using the standard technique. Limits of detection and quantification ranging from fmol L⁻¹ to pmol L⁻¹ with a wide linear range were obtained. The sensitivity and specificity of the methods were determined by constructing a ROC curve for predictive analysis and compared to the standard RT-PCR method.
SARS-CoV-2: colorimetric and electrochemical detection of viral RNA in human saliva samples
Keywords: COVID19; SARS-CoV-2; Electrochemical; Detection; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA